The Dynamics of Modernization Against the Tradition of Kalomba in Tana Toa Village, Kajang District, Bulukumba Regency - Megawaty Megawaty; Ika Andriani (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2018)
This study aims to determine (1) the effect of modernization on the traditional traditions of Kalomba in the village of Tana Toa (2) what is the meaning of the tool in the favorite tradition of Kalomba in Tana Toa village. This research was carried out in Tana Toa Village, Kajang District, Bulukumba District. The method used in this study is qualitative with a detailed approach and data collection used is interviews and observations. The results showed that there was no influence of modernization or changes to the traditional traditions of Kalomba in Desa Tana Toa, Kajang Subdistrict, in the common tradition of Kalomba, each contained a definite meaning or led to good things. In general, culture and customs have not changed at all, but socially, some Kajang tribal communities have changed due to the influence of the surrounding environment.